Up, up, and away : A Book about Adverbs - Ruth Heller's (New York Putnam Publishing Group,U.S., 1998)
"Lively...The playfully rhymed text flows effortlessly as it discusses superlatives, irregular adverbs, and double negatives....Informative and fun."-- "School Library Journal" "Using expansive color drawings and catchy rhymes, Heller writes about words frequently and vividly and with an unmistakable flourish....A clever introduction."-- "Booklist" "This eye-catching book explains its perplexing subject well and clearly, and more memorably than could any grammar textbook." -- "The Bulletin" of the Center for Children's Books
Keywords: Circle Time Book - Language Mechanics -- Circle Time Book - Language Mechanics